APPLICATION OF DIGITAL MARKETING TECHNOLOGIES IN A SOLAR POWER PLANT CONSTRUCTION COMPANY: THEORY AND PRACTICE - DIDENKO, Yevhen (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents a summary of the theory and practice of applying digital marketing technologies in a solar power plant construction company. It has been established that modern business development trends highlight the growing importance of digital marketing technologies as a key tool for achieving competitiveness. In the field of solar power plant construction, these technologies play a pivotal role in attracting clients, enhancing brand recognition, and promoting eco-friendly solutions. For companies in this industry to operate successfully, it is essential to adopt a comprehensive approach to marketing strategies. Key components include content marketing, SEO (search engine optimization), PPC advertising, and active engagement on social media platforms. These measures enable companies to not only effectively promote their services but also attract a target audience by emphasizing the environmental and economic benefits of solar energy. Modern CRM systems are an integral part of digital marketing, automating client interactions and helping tailor offerings to meet their needs. Web analytics tools, such as Google Analytics, combined with A/B testing methods, allow companies to refine their marketing campaigns and ensure the high efficiency of advertising initiatives. Innovative solutions also contribute to the industry’s development. They enable the creation of interactive tours for clients, demand forecasting, and personalized marketing messages. It has been determined that a crucial aspect of employing digital marketing technologies in a solar power plant construction company is the formation of a positive corporate image. Showcasing certifications, receiving industry awards, publishing client testimonials, and participating in trade exhibitions help build audience trust. This allows companies to establish long-term partnerships and maintain strong market positions.